Green Wakaf Instrument As A Sustainable Economy: A Systematic Literature Review - Ahmad Baihaqi Esaputra; Rafiq Azzam Al-Afif; Haryo Bimo Budi Indrasto (UNIVERSITAS PAKUAN, 2026)
This research endeavors to investigate the evolution and scholarly framework of green waqf as a mechanism for fostering a sustainable economy. The methodology employed is a descriptive qualitative approach, utilizing a Systematic Literature Review (SLR) in conjunction with bibliometric analysis. Data were sourced from the Scopus database through the keyword “green waqf,” subsequently filtered to encompass only journal articles. The analysis encompasses trends in publication, citation dynamics, networks of author collaboration, and thematic categorization of research subjects. The results suggest that green waqf research is currently in its nascent yet rapidly expanding phase, with a notable surge in publications anticipated post-2024. Indonesia is identified as the principal center of research activity, underscoring its pivotal role in the confluence of Islamic social finance and sustainability initiatives such as the Sustainable Development Goals (SDGs) and net-zero emissions commitments. The literature is delineated into several predominant themes, which include Islamic finance and environmental sustainability, frameworks for the green economy, contextual applications of waqf (e.g., agroforestry and pesantren), behavioral dimensions of waqf involvement, and governance alongside ESG concerns. Nevertheless, the study indicates that the research ecosystem is still fragmented, characterized by limited interscholarly collaboration and a predominance of conceptual studies over empirical investigations. This study makes a significant contribution by delineating the intellectual framework of green waqf research and pinpointing essential gaps, notably the deficiency of empirical data concerning environmental and economic repercussions. The findings yield pertinent implications for policymakers and waqf institutions aimed at improving standardization, enhancing transparency, and integrating green waqf within sustainable development frameworks.